La Sguardi planetari : La Generazione delle Immagini II. - Araeen, Rasheed; Lee, Yongwoo; Llanes, Llilian; Misiano, Viktor; Nanjo, Fumio; Pinto, Roberto; Senaldi, Marco; Serrano, Andres; Sorkin, Michael; Vantellini, Paolo; Venancio Filho, Paulo (Milano : Comune di Milano, 1996)
Araeen, Rasheed ; Brener, Alexander ; Bruguera, Tania ; Bruly-Bouabré, Frédéric ; Cai Guo-Qiang ; Caldas, Waltercio ; Chong, Ping ; Clark, Lygia ; Dias, Antonio ; Elagina, Elena ; Fang Lijun ; Girón, Mónica ; Grigely, Joseph ; Joo, Michael ; Kcho ; Kulik, Oleg ; Leiderman, Yuri ; Liticevskij, Georgij ; Lora, Marcos ; Makarevic, Igor ; Meireles, Cildo ; Moffatt, Tracey ; Munoz, Oscar ; Murakami, Takashi ; Neshat, Shirin ; Oiticica, Hélio ; Osmolovskij, Anatolij ; Resende, José ; Segura, Esterio ; Serrano, Andres ; Tunga ; Uribe, Carlos ; Wen, Lee
Engels & Italiaans
Sguardi planetari : La Generazione delle Imagini II, Comune di Milano, 1995/1996
boek